Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

How old are the Mojave topographic dunes? The implications of new luminescence dating analyses from the Cady Mountains, Mojave Desert, southwest USA - Andrew S. Carr; Alex S. Hay; Mark D. Bateman; Ian Livingstone; D. Mark Powell (Geomorphology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

The roles of heating rate, intensity, and duration on the response of corals and their endosymbiotic algae to thermal stress - Nicolas R. Evensen; Timothy G. Bateman; Courtney N. Klepac; Sebastian Schmidt-Roach; Marcelle Barreto; Manuel Aranda; Mark E. Warner; Daniel J. Barshis (Journal of Experimental Marine Biology and Ecology, 2023)

DNA metabarcoding identifies urban foraging patterns of oligolectic and polylectic cavity-nesting bees - Kristen Fernandes; Kit Prendergast; Philip W. Bateman; Benjamin J. Saunders; Mark Gibberd; Michael Bunce; Paul Nevill (Oecologia, 2022)
Urbanisation modifies natural landscapes resulting in built-up space that is covered by buildings or hard surfaces and managed green spaces that often substitute native plant species with exotics. Some native bee species have been able to adapt to urban environments, foraging and reproducing in these highly modified areas. However, little is known on how the foraging ecology of native bees is affected by urbanised environments, and whether impacts vary among species with different degrees of specialisation for pollen collection. Here, we aim to investigate the responses of native bee foraging behaviour to urbanisation, using DNA metabarcoding to identify the resources within nesting tubes. We targeted oligolectic (specialist) and polylectic (generalist) cavity-nesting bee species in residential gardens and remnant bushland habitats. We were able to identify 40 families, 50 genera, and 23 species of plants, including exotic species, from the contents of nesting tubes. Oligolectic bee species had higher diversity of plant pollen in their nesting tubes in residential gardens compared to bushland habitats, along with significantly different forage composition between the two habitats. This result implies a greater degree of forage flexibility for oligolectic bee species than previously thought. In contrast, the diversity and composition of plant forage in polylectic bee nesting tubes did not vary between the two habitat types. Our results suggest a complex response of cavity-nesting bees to urbanisation and support the need for additional research to understand how the shifts in foraging resources impact overall bee health.

Exploring controls of the early and stepped deglaciation on the western margin of the British Irish Ice Sheet - Sara Benetti; Richard C. Chiverrell; Colm Ó Cofaigh; Matt Burke; Alicia Medialdea; David Small; Colin Ballantyne; Mark D. Bateman; S. Louise Callard; Peter Wilson; Derek Fabel; Chris D. Clark; et al. (Journal of Quaternary Science, 2021)
New optically stimulated luminescence dating and Bayesian models integrating all legacy and BRITICE‐CHRONO geochronology facilitated exploration of the controls on the deglaciation of two former sectors of the British–Irish Ice Sheet, the Donegal Bay (DBIS) and Malin Sea ice‐streams (MSIS). Shelf‐edge glaciation occurred ~27 ka, before the global Last Glacial Maximum, and shelf‐wide retreat began 26–26.5 ka at a rate of ~18.7–20.7 m a –1 . MSIS grounding zone wedges and DBIS recessional moraines show episodic retreat punctuated by prolonged still‐stands. By ~23–22 ka the outer shelf (~25 000 km 2 ) was free of grounded ice. After this time, MSIS retreat was faster (~20 m a –1 vs. ~2–6 m a –1 of DBIS). Separation of Irish and Scottish ice sources occurred ~20–19.5 ka, leaving an autonomous Donegal ice dome. Inner Malin shelf deglaciation followed the submarine troughs reaching the Hebridean coast ~19 ka. DBIS retreat formed the extensive complex of moraines in outer Donegal Bay at 20.5–19 ka. DBIS retreated on land by ~17–16 ka. Isolated ice caps in Scotland and Ireland persisted until ~14.5 ka. Early retreat of this marine‐terminating margin is best explained by local ice loading increasing water depths and promoting calving ice losses rather than by changes in global temperatures. Topographical controls governed the differences between the ice‐stream retreat from mid‐shelf to the coast.

Pattern, style and timing of British–Irish Ice Sheet advance and retreat over the last 45 000 years: evidence from NW Scotland and the adjacent continental shelf - Tom Bradwell; Derek Fabel; Chris D. Clark; Richard C. Chiverrell; David Small; Rachel K. Smedley; Margot H. Saher; Steven G. Moreton; Dayton Dove; S. Louise Callard; Geoff A. T. Duller; Alicia Medialdea; et al. (Journal of Quaternary Science, 2021)
Predicting the future response of ice sheets to climate warming and rising global sea level is important but difficult. This is especially so when fast‐flowing glaciers or ice streams , buffered by ice shelves, are grounded on beds below sea level. What happens when these ice shelves are removed? And how do the ice stream and the surrounding ice sheet respond to the abruptly altered boundary conditions? To address these questions and others we present new geological, geomorphological, geophysical and geochronological data from the ice‐stream‐dominated NW sector of the last British–Irish Ice Sheet (BIIS). The study area covers around 45 000 km 2 of NW Scotland and the surrounding continental shelf. Alongside seabed geomorphological mapping and Quaternary sediment analysis, we use a suite of over 100 new absolute ages (including cosmogenic‐nuclide exposure ages, optically stimulated luminescence ages and radiocarbon dates) collected from onshore and offshore, to build a sector‐wide ice‐sheet reconstruction combining all available evidence with Bayesian chronosequence modelling. Using this information we present a detailed assessment of ice‐sheet advance/retreat history, and the glaciological connections between different areas of the NW BIIS sector, at different times during the last glacial cycle. The results show a highly dynamic, partly marine, partly terrestrial, ice‐sheet sector undergoing large size variations in response to sub‐millennial‐scale climatic (Dansgaard–Oeschger) cycles over the last 45 000 years. Superimposed on these trends we identify internally driven instabilities, operating at higher frequency, conditioned by local topographic factors, tidewater dynamics and glaciological feedbacks during deglaciation. Specifically, our new evidence indicates extensive marine‐terminating ice‐sheet glaciation of the NW BIIS sector during Greenland Stadials 12 to 9 – prior to the main ‘Late Weichselian’ ice‐sheet glaciation. After a period of restricted glaciation, in Greenland Interstadials 8 to 6, we find good evidence for rapid renewed ice‐sheet build‐up in NW Scotland, with the Minch ice‐stream terminus reaching the continental shelf edge in Greenland Stadial 5, perhaps only briefly. Deglaciation of the NW sector took place in numerous stages. Several grounding‐zone wedges and moraines on the mid‐ and inner continental shelf attest to significant stabilizations of the ice‐sheet grounding line, or ice margin, during overall retreat in Greenland Stadials 3 and 2, and to the development of ice shelves. NW Lewis was the first substantial present‐day land area to deglaciate, in the first half of Greenland Stadial 3 at a time of globally reduced sea‐level c. 26 ka bp , followed by Cape Wrath at c. 24 ka bp. The topographic confinement of the Minch straits probably promoted ice‐shelf development in early Greenland Stadial 2, providing the ice stream with additional support and buffering it somewhat from external drivers. However, c. 20–19 ka bp , as the grounding‐line migrated into shoreward deepening water, coinciding with a marked change in marine geology and bed strength, the ice stream became unstable. We find that, once underway, grounding‐line retreat proceeded in an uninterrupted fashion with the rapid loss of fronting ice shelves – first in the west, then the east troughs – before eventual glacier stabilization at fjord mouths in NW Scotland by ~17 ka bp. Around the same time, ~19–17 ka bp , ice‐sheet lobes readvanced into the East Minch – possibly a glaciological response to the marine‐instability‐triggered loss of adjacent ice stream (and/or ice shelf) support in the Minch trough. An independent ice cap on Lewis also experienced margin oscillations during mid‐Greenland Stadial 2, with an ice‐accumulation centre in West Lewis existing into the latter part of Heinrich Stadial 1. Final ice‐sheet deglaciation of NW mainland Scotland was punctuated by at least one other coherent readvance at c. 15.5 ka bp , before significant ice‐mass losses thereafter. At the glacial termination, c. 14.5 ka bp , glaciers fed outwash sediment to now‐abandoned coastal deltas in NW mainland Scotland around the time of global Meltwater Pulse 1A. Overall, this work on the BIIS NW sector reconstructs a highly dynamic ice‐sheet oscillating in extent and volume for much of the last 45 000 years. Periods of expansive ice‐sheet glaciation dominated by ice‐streaming were interspersed with periods of much more restricted ice‐cap or tidewater/fjordic glaciation. Finally, this work indicates that the role of ice streams in ice‐sheet evolution is complex but mechanistically important throughout the lifetime of an ice sheet – with ice streams contributing to the regulation of ice‐sheet health but also to the acceleration of ice‐sheet demise via marine ice‐sheet instabilities.

Retreat dynamics of the eastern sector of the British–Irish Ice Sheet during the last glaciation - David J. A. Evans; David H. Roberts; Mark D. Bateman; Chris D. Clark; Alicia Medialdea; Louise Callard; Elena Grimoldi; Richard C. Chiverrell; Jeremy Ely; Dayton Dove; Colm Ó Cofaigh; Margot Saher; et al. (Journal of Quaternary Science, 2021)
The findings of BRITICE‐CHRONO Transect 2 through the North Sea Basin and eastern England are reported. We define ice‐sheet marginal oscillation between ~31 and 16 ka, with seven distinctive former ice‐sheet limits (L1–7) constrained by Bayesian statistical analysis. The southernmost limit of the North Sea Lobe is recorded by the Bolders Bank Formation (L1; 25.8–24.6 ka). L2 represents ice‐sheet oscillation and early retreat to the northern edge of the Dogger Bank (23.5–22.2 ka), with the Garret Hill Moraine in north Norfolk recording a significant regional readvance to L3 at 21.5–20.8 ka. Ice‐marginal oscillations at ~26–21 ka resulted in L1, L2 and L3 being partially to totally overprinted. Ice‐dammed lakes related to L1–3, including Lake Humber, are dated at 24.1–22.3 ka. Ice‐sheet oscillation and retreat from L4 to L5 occurred between 19.7 and 17.3 ka, with grounding zone wedges marking an important transition from terrestrial to marine tidewater conditions, triggered by the opening of the Dogger Lake spillway between 19.9 and 17.5 ka. L6 relates to ice retreat under glacimarine conditions and final ice retreat into the Firth of Forth by 15.8 ka. L7 (~15 ka) represents an ice retreat from Bosies Bank into the Moray Firth.

The evolution of the terrestrial‐terminating Irish Sea glacier during the last glaciation - Richard Christopher Chiverrell; Geoff Stephen Powell Thomas; Matthew Burke; Alicia Medialdea; Rachel Smedley; Mark Bateman; Chris Clark; Geoffrey A. T. Duller; Derek Fabel; Geraint Jenkins; Xianjiao Ou; Helen Marie Roberts; et al. (Journal of Quaternary Science, 2021)
Here we reconstruct the last advance to maximum limits and retreat of the Irish Sea Glacier (ISG), the only land‐terminating ice lobe of the western British Irish Ice Sheet. A series of reverse bedrock slopes rendered proglacial lakes endemic, forming time‐transgressive moraine‐ and bedrock‐dammed basins that evolved with ice marginal retreat. Combining, for the first time on glacial sediments, optically stimulated luminescence (OSL) bleaching profiles for cobbles with single grain and small aliquot OSL measurements on sands, has produced a coherent chronology from these heterogeneously bleached samples. This chronology constrains what is globally an early build‐up of ice during late Marine Isotope Stage 3 and Greenland Stadial (GS) 5, with ice margins reaching south Lancashire by 30 ± 1.2 ka, followed by a 120‐km advance at 28.3 ± 1.4 ka reaching its 26.5 ± 1.1 ka maximum extent during GS‐3. Early retreat during GS‐3 reflects piracy of ice sources shared with the Irish‐Sea Ice Stream (ISIS), starving the ISG. With ISG retreat, an opportunistic readvance of Welsh ice during GS‐2 rode over the ISG moraines occupying the space vacated, with ice margins oscillating within a substantial glacial over‐deepening. Our geomorphological chronosequence shows a glacial system forced by climate but mediated by piracy of ice sources shared with the ISIS, changing flow regimes and fronting environments.

Pattern, style and timing of British–Irish Ice Sheet retreat: Shetland and northern North Sea sector - Tom Bradwell; David Small; Derek Fabel; Chris D. Clark; Richard C. Chiverrell; Margot H. Saher; Dayton Dove; S. Louise Callard; Matthew J. Burke; Steven G. Moreton; Alicia Medialdea; Mark D. Bateman; et al. (Journal of Quaternary Science, 2021)
The offshore sector around Shetland remains one of the least well‐studied parts of the former British–Irish Ice Sheet with several long‐standing scientific issues unresolved. These key issues include (i) the dominance of a locally sourced ‘Shetland ice cap’ vs an invasive Fennoscandian Ice Sheet; (ii) the flow configuration and style of glaciation at the Last Glacial Maximum (i.e. terrestrial vs marine glaciation); (iii) the nature of confluence between the British–Irish and Fennoscandian Ice Sheets; (iv) the cause, style and rate of ice sheet separation; and (v) the wider implications of ice sheet uncoupling on the tempo of subsequent deglaciation. As part of the Britice‐Chrono project, we present new geological (seabed cores), geomorphological, marine geophysical and geochronological data from the northernmost sector of the last British–Irish Ice Sheet (north of 59.5°N) to address these questions. The study area covers ca. 95 000 km 2 , an area approximately the size of Ireland, and includes the islands of Shetland and the surrounding continental shelf, some of the continental slope, and the western margin of the Norwegian Channel. We collect and analyse data from onshore in Shetland and along key transects offshore, to establish the most coherent picture, so far, of former ice‐sheet deglaciation in this important sector. Alongside new seabed mapping and Quaternary sediment analysis, we use a multi‐proxy suite of new isotopic age assessments, including 32 cosmogenic‐nuclide exposure ages from glacially transported boulders and 35 radiocarbon dates from deglacial marine sediments, to develop a synoptic sector‐wide reconstruction combining strong onshore and offshore geological evidence with Bayesian chronosequence modelling. The results show widespread and significant spatial fluctuations in size, shape and flow configuration of an ice sheet/ice cap centred on, or to the east of, the Orkney–Shetland Platform, between ~30 and ~15 ka BP. At its maximum extent ca. 26–25 ka BP , this ice sheet was coalescent with the Fennoscandian Ice Sheet to the east. Between ~25 and 23 ka BP the ice sheet in this sector underwent a significant size reduction from ca. 85 000 to 2 , accompanied by several ice‐margin oscillations. Soon after, connection was lost with the Fennoscandian Ice Sheet and a marine corridor opened to the east of Shetland. This triggered initial (and unstable) re‐growth of a glaciologically independent Shetland Ice Cap ca. 21–20 ka BP with a strong east–west asymmetry with respect to topography. Ice mass growth was followed by rapid collapse, from an area of ca. 45 000 km 2 to ca. 15 000 km 2 between 19 and 18 ka BP , stabilizing at ca. 2000 km 2 by ~17 ka BP. Final deglaciation of Shetland occurred ca. 17–15 ka BP , and may have involved one or more subsidiary ice centres on now‐submerged parts of the continental shelf. We suggest that the unusually dynamic behaviour of the northernmost sector of the British–Irish Ice Sheet between 21 and 18 ka BP – characterized by numerous extensive ice sheet/ice mass readvances, rapid loss and flow redistributions – was driven by significant changes in ice mass geometry, ice divide location and calving flux as the glaciologically independent ice cap adjusted to new boundary conditions. We propose that this dynamism was forced to a large degree by internal (glaciological) factors specific to the strongly marine‐influenced Shetland Ice Cap.

An asymmetric producer-scrounger game: body size and the social foraging behavior of coho salmon - Jessica A. Phillips; Stephanie J. Peacock; Andrew Bateman; Mackenzie Bartlett; Mark A. Lewis; Martin Krkošek (Theoretical Ecology, 2018)

Sedimentation during Marine Isotope Stage 3 at the eastern margins of the Glacial Lake Humber basin, England - David J. A. Evans; David H. Roberts; Mark D. Bateman; Alicia Medialdea; Jeremy Ely; Steven G. Moreton; Chris D. Clark; Derek Fabel (Journal of Quaternary Science, 2018)
The stratigraphic sequence at North Cave, on the eastern margins of the Lake Humber basin, records the deposition of a fluvioperiglacial fan (LFs 1–4), with early sedimentation (LF1) dating to Marine Isotope Stage (MIS) 3 (optically stimulated luminescence date range 41.8–38.6 ka and 14 C dates 41.6–49 ka BP). Three phases of permafrost and ice wedge development during MIS 3 are evident and indicate possible fan abandonment and hence periods of reduced nival runoff. Involution structures dated to 11.1 ka with large boulders and fine‐grained sorted circles in LF4b are interpreted as periglacially cryoturbated littoral deposits with boulders derived from anchor ice, initially deposited at the margins of Lake Humber up to an altitude of 8 m OD during MIS 2. The style and age of fluvioperiglacial fan deposition at North Cave is compatible with several mid‐Devensian sites around Britain characterized by significant nival melt and run‐off from steeply incised valleys in permafrozen cuesta landscapes. This phase of fluvioperiglacial fan aggradation to near or below 0 m OD is recorded around the glacial lakes Humber and Fenland basins and indicates that no glacial lakes existed at that time.

Glacial Lake Pickering: stratigraphy and chronology of a proglacial lake dammed by the North Sea Lobe of the British–Irish Ice Sheet - David J. A. Evans; Mark D. Bateman; David H. Roberts; Alicia Medialdea; Laura Hayes; Geoff A. T. Duller; Derek Fabel; Chris D. Clark (Journal of Quaternary Science, 2017)
We report the first chronology, using four new optically stimulated luminescence dates, on the sedimentary record of Glacial Lake Pickering, dammed by the North Sea Lobe of the British–Irish Ice Sheet during the Dimlington Stadial (24–11 ka cal BP). Dates range from 17.6 ± 1.0 to 15.8 ± 0.9 ka for the sedimentation of the Sherburn Sands at East Heslerton, which were formed by multiple coalescing alluvial fans prograding into the falling water levels of the lake and fed by progressively larger volumes of debris from the Wolds. Fan formation ceased ∼15.8 ka, at a time when permafrost was degrading and nival‐fed streams were no longer capable of supplying sediment to the fans. A further age of 10.1 ± 0.7 ka dates the reworking of coversand into the early part of the Holocene, immediately post‐dating Younger Dryas periglacial structures. A 45‐m lake level dates to ∼17.6 ka, when the North Sea Lobe was already in retreat, having moved eastward of the Wykeham Moraine; it stood further east at the Flamborough Moraine by ∼17.3 ka. The highest (70 m) lake level and the occupation of the Wykeham Moraine date to an earlier phase of the North Sea Lobe occupation of the Vale of Pickering.

The dynamics of coupled populations subject to control - Stephanie J. Peacock; Andrew W. Bateman; Martin Krkošek; Mark A. Lewis (Theoretical Ecology, 2016)

A late Pleistocene–Holocene multi‐proxy record of palaeoenvironmental change from Still Bay, southern Cape Coast, South Africa - Lynne J. Quick; Andrew S. Carr; Michael E. Meadows; Arnoud Boom; Mark D. Bateman; David L. Roberts; Paula J. Reimer; Brian M. Chase (Journal of Quaternary Science, 2015)
The southern Cape is a key focus for southern African palaeoenvironmental research as it represents the transitional region between temperate westerlies and sub‐tropical rainfall sources. This study presents pollen, plant biomarker, geochemical and charcoal data preserved in the Rietvlei wetland. The bulk of the record spans the last 16 ka, but it also provides rare insights into late Marine Oxygen Isotope Stage (MIS) 3 (ca. 35–30k cal a BP). The data suggest that during the Pleistocene the development and permanence of this wetland was probably influenced by sea‐level change via control on the local water table; notably lower sea levels within MIS 2 resulted in very limited wetland productivity. The MIS 3 section provides evidence both supporting previous suggestions of relatively humid conditions, but also some indication of periodic arid phases. The Holocene record suggests clear contrasts between the early (11–7k cal a BP; relatively humid), mid‐Holocene (7–3.3k cal a BP; more arid, less productive wetland conditions) and latest Holocene (last 2k cal a BP; resurgence in both fynbos and aquatic/riparian pollen). While isolating the roles of winter/summer rainfall remains challenging, these data clarify the nature of change during key episodes in the regional palaeoenvironmental record.

Inland aeolian deposits of south‐west France: facies, stratigraphy and chronology - Pascal Bertran; Mark D. Bateman; Marion Hernandez; Norbert Mercier; Dominique Millet; Luca Sitzia; Jean‐Pierre Tastet (Journal of Quaternary Science, 2011)
Archaeological investigations undertaken along a proposed highway together with the compilation of available geological and pedological data made it possible to give a first overview of the distribution of Pleistocene aeolian deposits in south‐west France. A chronological framework for deposition has been obtained using both radiocarbon ( n = 24) and luminescence ( n = 26) dating. It shows that aeolian transport was very active during the Late Pleniglacial, between 15 and ∼23 ka, leading to sand emplacement over a 13 000‐m 2 area at the centre of the basin. The Pleniglacial coversands are typified by extensive fields of small transverse to barchanoid ridges giving way to sandsheets to the east. Subsequent aeolian phases, at ca. 12 ka (Younger Dryas) and 0.8–0.2 ka (Little Ice Age), correspond to the formation of more localized and higher, mainly parabolic dunes. At the southern and eastern margins of the coversand area, aeolian dust accumulated to form loess deposits, the thickness of which reaches ∼3 m on the plateaus. Luminescence dates together with interglacial‐ranking palaeoluvisols between the loess units clearly indicate that these accumulations built up during the last two glacial–interglacial cycles. The chronology of sand and loess deposition thus appears to be consistent with that already documented for northern Europe. This suggests that it was driven by global climate changes in the northern hemisphere. The relatively thin aeolian deposits (and particularly loess) in south‐west France is thought to reflect both a supply‐limited system and a moister climate than in more northern and continental regions. Copyright © 2011 John Wiley & Sons, Ltd.

Understanding geomorphic responses to environmental change: a 19 000‐year case study from semi‐arid central Texas, USA - Claire Boulter; Mark D. Bateman; Charles D. Frederick (Journal of Quaternary Science, 2010)
Understanding the impact of past climatic changes on landscape stability is crucial in order to predict and mitigate the effects of future changes. However, in arid and semi‐arid environments, reconstructions are often hampered by a poor understanding of the relationship between sediment deposition and climate. We present here data from central Texas, a region that is sensitive to environmental change but has received relatively little attention. The study integrates a chronology of 29 optically stimulated luminescence (OSL) ages from six sedimentary sites in a range of depositional contexts with a 19 000 a climate record derived from pollen extracted from the adjacent Boriack Bog. By comparing the two records, we aimed to assess the relationship between climate change and geomorphic activity. Data show that extensive aeolian and colluvial deposition occurred during the mid to late Holocene, with sedimentation generally increasing during more arid phases. However, a number of depositional events on slopes were associated with moister episodes, and sediment was also deposited in a summit setting immediately after phases of increased precipitation. Linkages between climate change and geomorphic response were therefore complex, being controlled by both sediment supply and transport energy. The climatic fluctuations identified in the Boriack Bog record highlight the sensitivity of central Texas to environmental change, while disparities in conditions recorded between it and other palaeoenvironmental sites in the southern USA emphasise the need for further work in order to enhance understanding of landscape sedimentary response to climate. Copyright © 2010 John Wiley & Sons, Ltd.

Luminescence dating indicates radiocarbon age underestimation in late Pleistocene fluvial deposits from eastern England - Rebecca M. Briant; Mark D. Bateman (Journal of Quaternary Science, 2009)
Robust geochronological control is crucial for interpreting and correlating the environmental record from fragmentary terrestrial sequences from the last glacial period. Traditional terrestrial stratigraphies are typically reliant on radiocarbon dating, although estimates of antiquity for samples older than 40 ka may be unreliable. Optically stimulated luminescence (OSL) dating of sediments is an alternative for dating the whole of the last glacial period and also provides the opportunity to independently test radiocarbon based chronologies. This paper presents a set of nine directly comparable paired OSL and accelerator mass spectrometry (AMS) radiocarbon ages from multiple sites within Devensian fluvial sediments in lowland Britain and shows that it is possible to obtain robust OSL age estimates throughout this time period. The two techniques agree well for ages younger than ca. 29 14 C ka BP (ca. 35 cal. ka BP) but disagree beyond ca. 35 14 C ka BP (ca. 40 cal. ka BP). This is thought to be due to radiocarbon ages on older organic material having been contaminated by low levels of modern carbon. It is therefore suggested that all conventionally pre‐treated radiocarbon ages greater than 35 14 C ka BP should be treated with extreme caution. Copyright © 2009 John Wiley & Sons, Ltd.

First evidence for episodic flooding events in the arid interior of central Saudi Arabia over the last 60 ka - Sue J. McLaren; Farhan Al‐Juaidi; Mark D. Bateman; Andrew C. Millington (Journal of Quaternary Science, 2009)
Although evidence for Quaternary environmental changes in the Arabian Peninsula is now growing, research has mostly been conducted in the United Arab Emirates (UAE) and in the Sultanate of Oman. There have been virtually no recent studies in Saudi Arabia, especially in the central region such as around Al‐Quwaiayh. In this area there are a series of outwash plains developed along the eastern edge of the Arabian Shield that formed in the late Quaternary. Four sedimentary sections, which are representative of the deposits that have accumulated, have been studied and five luminescence ages obtained. These are the first luminescence ages acquired from Quaternary sediments in central Saudi Arabia. The preserved fluvial deposits in the study area have formed during humid events at ca. 54 ka, ca. 39 ka and ca. 0.8 ka. In more recent times aeolian sands have been encroaching on to the distal parts of the outwash plains. Copyright © 2008 John Wiley & Sons, Ltd.

The timing of last‐glacial periglacial and aeolian events, Twente, eastern Netherlands - Mark D. Bateman; Jacobus Van Huissteden (Journal of Quaternary Science, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)